2023
DOI: 10.3390/ijms24065419
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy and ER Stress Induced by Palmitate Are Counteracted by Mango Peel and Seed Extracts in 3T3-L1 Adipocytes

Abstract: A diet rich in saturated fatty acids (FAs) has been correlated with metabolic dysfunction and ROS increase in the adipose tissue of obese subjects. Thus, reducing hypertrophy and oxidative stress in adipose tissue can represent a strategy to counteract obesity and obesity-related diseases. In this context, the present study showed how the peel and seed extracts of mango (Mangifera indica L.) reduced lipotoxicity induced by high doses of sodium palmitate (PA) in differentiated 3T3-L1 adipocytes. Mango peel (MPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…To assess the intracellular generation of reactive oxygen species (ROS), cells were plated in 96-well plates and allowed to adhere overnight. Cells were treated with MG and incubation with 5-(and-6)-carboxy-2′,7′-dichlorodihydrofluorescein diacetate (H2DCFDA) fluorochrome (Molecular Probe; Thermo Fisher Scientific, Inc., Life Technologies Italia, Monza, Italy) was performed as previously reported [ 37 ]. For this purpose, stock solutions of H2DCFDA were dissolved in DMSO and aliquots were stored at −20 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the intracellular generation of reactive oxygen species (ROS), cells were plated in 96-well plates and allowed to adhere overnight. Cells were treated with MG and incubation with 5-(and-6)-carboxy-2′,7′-dichlorodihydrofluorescein diacetate (H2DCFDA) fluorochrome (Molecular Probe; Thermo Fisher Scientific, Inc., Life Technologies Italia, Monza, Italy) was performed as previously reported [ 37 ]. For this purpose, stock solutions of H2DCFDA were dissolved in DMSO and aliquots were stored at −20 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded in a 96-well plate at a density of 6 × 10 3 cells/well. Then, cells were treated with different concentrations (5–15 µM) for 24–72 h. At the end of the incubation time, we added a solution of MTT (3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide; Sigma-Aldrich) at a concentration of 11 mg/mL in PBS and incubated for 2 h at 37 °C, as previously described [ 96 ]. Finally, 100 µL/well of lysis buffer (20% sodium dodecyl sulphate in 50% N,N-dimethylformamide, pH 4.0) was added and incubated for three hours at 37 °C to solubilize formazan.…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that upregulation of HO-1 can reduce the expression of CHOP, a key mediator of ER stress, thereby alleviating ER stress (Pratelli et al, 2023). To note, ginsenoside Rb2 has been discovered to activate the GPR120/AMPK/HO-1 pathway, lowering eIF2α and CHOP expression in LPS-induced HUVECs and THP-1 monocytes.…”
Section: Anti-apoptotic Effectmentioning
confidence: 99%